Dynamic assessment of parathyroid function in acute malaria - Davis, T.M.E; Balbir, Singh; Choo, KE; Ibrahim, J.; Sulaiman, S.A.; Kadir, ZA; Ismail, R (Wiley, 1998)
Objectives. To investigate the dynamic parathyroid response to rapidly induced, sustained hypocalcaemia in patients with acute malaria and in healthy volunteers. Design. Serum intact parathormone (PTH) concentrations were measured on samples taken before and during a variable-rate tri-sodium citrate infusion designed to ‘clamp’ the whole blood ionised calcium concentration 0.20 mmol L21 below baseline for 120 min. Subjects. Six Malaysian patients aged 17–42 years with acute malaria, four of whom were restudied in convalescence, and 12 healthy controls aged 19–36 years. Main outcome measures. Whole-blood ionised calcium and serum intact PTH concentrations.